The passive CNV: carving out the contribution of task-related processes to expectancy - Mento, Giovanni (Frontiers in Human Neuroscience, 2013)
In this perspective article, I summarized certain theoretical and methodological issues concerning the investigation of the contribution of cognitive and motor processes to the electrophysiological stimulus-preceding activity. In particular, the question of whether the contingent negative variation (CNV) is a marker reflecting both cognitive expectancy and motor preparation in the S1–S2 paradigms was discussed. New evidence suggests that it is possible to isolate an automatic temporal expectancy-related cognitive mechanism relying on a passive CNV after ruling out the contribution of task-related processes, including motor and decisional processes, to it. This can be achieved by simply manipulating the trial temporal structure according to a probabilistic, oddball distribution. The scientific value of this finding is framed within a historical perspective in the attempt to bridge together the classic literature linking the CNV to stimulus preparation and the more recently published literature linking the CNV to temporal processing.